METODE TARGHIB WA TARHIB DALAM PENDIDIKAN ISLAM - Prahara, Erwin Yudi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: It is asserted that method in education is one determinant of success. In Islamic education, there is a popular method called Targhib wa tarhib, but unfortunately it is less popular in a last few decades because many Islamic educators prefer western educational concept which tends to disregard the affective aspect which can eliminate the purpose of education that is simultaneously to form intelligent human intellectually andspiritually. Besides, this method comes from al-Quran and al-Hadith that is certainly true because according to human development both from the aspect of spiritual or physical. In accord to this, the application of Targhib wa tarhib in contemporary times is very important in both formal and non-formal education with contextually relevant designs. Hence, the religious and psychological values of Tarhib wa targhib method can be established.Â Ø¨ÙØºØªØ±ÙØ§Â« Ø©ÙÙØ±Ø· Ø©ÙÙÙØ§Ø³ÙØ¥Ø§ Ø©ÙØ¨ØªØ±ÙØ§ ÙÙÙ .Ø©ÙØ¨ØªØ±ÙØ§ ØØ§ÙØ¬ ÙÙ Ø©ÙØ³Ø§Ø³ÙØ£Ø§ Ø±ØµØ§ÙØ¹ÙØ§ Ø¯ØØ£ Ø©ÙØ¨ØªØ±ÙØ§ Ø©ÙÙØ±Ø· Ø±Ø§ÙØªØ®Ø§ ÙØ§ÙÂ ØªØ§ÙØ±Ø¸ÙÙØ§ ÙÙ Ø©ÙØ¨ØªØ±ÙØ§ Ø¹ÙÙ ÙÙØ¥ ÙÙÙÙÙÙ ÙÙØ³Ø±Ø¯ÙÙØ§ ÙÙ ÙØ±Ø«Ù Ø©ÙØ±Ø®ÙØ£Ø§ Ø©ÙÙÙØ¢Ø§ ÙÙ ÙØ³ÙØ£Ø§ Ù ÙÙÙÙ ØØ©Ø±ÙÙØ´Ù ÙÙÙ Â»Ø¨ÙÙØªØ±ÙØ§ÙÂ Ø©ÙÙØ«ÙÙØ§ Ø©ÙØµØ®Ø´ÙØ§ ÙÙÙÙØª ( Ø©ÙØ¨ØªØ±ÙØ§ ÙÙ Ø©ÙØ³Ø§Ø³ÙØ£Ø§ ÙØ§Ø¯ÙÙØ£Ø§ Ø¹Ø§ÙØ¶ ÙÙ Ø±Ø«Ø¤ÙÙØ§ ÙÙØ±ØØ³ÙÙÙØ§ Ø¨ÙØ§Ø¬ÙÙ Ø©ÙÙÙÙÙØ§ Ø©ÙØ¨Ø±ØºÙØ§Â ÙØ§Ù â Ø©ÙØ³ÙØ§Ù ÙØ¢Ø±ÙÙØ§ ÙÙØ¥ Ø©Ø¯ÙØªØ³Ù Ø©ÙÙØ±Ø·ÙØ§ ÙØ°Ù ØªÙØ§Ù ÙÙØ° Ø¨ÙØ§Ø¨Ø¬Ù .)Ø¡Ø§ÙØ³ Ù Ø¯Ø ÙÙØ¹ Ø§Ø¶ÙØ£ Ø©ÙÙ ÙØ¯ØªÙ ÙÙÙ Ø§ÙÙØ±Ø¹ÙÂ ÙÙØ¨Ø·Øª Ù ÙÙÙ Ø§Ø°ÙØ¨ .ÙÙØ§ÙØ³ÙØ¬Ø§ Ø¨ÙØ§ÙØ¬Ø§Ù ÙØÙØ±ÙØ§ Ø¨ÙØ§ÙØ¬Ø§ ÙÙ ÙØ§Ø³ÙÙØ¥Ø§ Ø±Ù ÙØ·Øª ÙØ§Ø±ÙØ§Ø³Ù Ø§ÙÙÙØ£Ù â ÙØ Ø§ÙÙÙØ£ ÙÙ Ø¨ÙØ±Â .ÙØ³ÙÙÙØ§ Ø¨ÙØ§ÙØ¬Ø§ ÙØ£ ÙØÙØ±ÙØ§ ÙÙÙØ¯ÙØ§ Ø¨ÙØ§ÙØ¬Ø§ ÙÙ ÙØ§ÙØ£ Ø¡Ø§ÙØ³ Â« Ø¨ÙÙØªØ±ÙØ§Ù Ø¨ÙØºØªØ±ÙØ§ Â« Ø¨ÙÙØ³Ø£